ANTIBIOTIC SUSCEPTIBILITY PATTERNS OF DIFFERENT BACTERIA ISOLATED FROM PATIENTS WITH VENTILATOR ASSOCIATED PNEUMONIA (VAP) - Alqurashi, Abdulrahman M. (Medknow Publications & Media Pvt Ltd, 2005)
OBJECTIVE: Ventilator associated pneumonia (VAP) is a frequent complication of mechanical ventilation (MV) and it is a leading cause of death in MV patients. The development of VAP has been demonstrated as being due to aspiration of oropharyngeal secretion, ventilator tubing condensate, or gastric contents that are colonized with pathogenic microorganisms. The aim of the present study is to isolate and identify bacteria that cause VAP and to study antibiotic susceptibility. MATERIAL AND METHODS: This study was carried out on 95 patients who fulfilled the diagnostic criteria for VAP. Quantitative cultures of endotracheal aspirates (EA) using a cut-off point of 10(6) cfu/ml was done. RESULTS: The microbiological results revealed that gram negative bacilli were the most common bacterial agents responsible for VAP and accounted for 78.8% of all the causative agents. The most common isolated organisms were Klebsiella pnemouniae (30.9 %) followed by Pseudomonas aeruginosa (22.5%), Staphylococcus aureus (21.2%), Eschericia coli (12.8 %), Proteus spp. (9.8%), and Citrobacter spp. (2.8%). Blood cultures were positive in 25.9% of patients with Klebsiella pnemouniae in about 33.3%. CONCLUSION: From this study, it can be concluded that VAP is an important nosocomial infection. EA is a simple procedure to obtain respiratory samples and perform sensitivity testing in patients with VAP. Also, the commonest cause of VAP is gram negative bacilli.